Creativity within a military setting: assessing the utility of an existing military visual aid to facilitate military deception amongst a civilian population - O'Malley, Callum A.; Harris, David J.; Arthur, Tom; Blackford, Hannah; Raywood-Burke, George; Jones, Nigel; Vine, Samuel J. (Frontiers in Psychology, 2025)
IntroductionDeception can function as a useful tool for any military figure. Historic examples demonstrate that deception facilitates success by corralling an adversary into failure. Traits such as creativity and imagination are considered of central importance to devising useful and effective deceptive ideas. In lieu of being naturally creative/imaginative, visual aids highlighting core military deception principles could offset these shortcomings. This study assessed whether an existing military deception visual aid improved the number, usefulness, and originality of deceptive ideas amongst a civilian population.MethodsAn independent samples design comprising 80 participants (44 female) were equally assigned to an experimental (with aid) or control (without aid) group. Participants created as many deceptive stratagems in as much detail as possible, during a 15-minute hypothetical task scenario. The number of stratagems and ratings of the usefulness, originality, and a snapshot score of the participant's self-selected best stratagem were compared between experimental groups.Results and discussionNo significant differences emerged for the number of stratagems (p = 0.061, r = 0.238) or usefulness (p = 0.348, r = 0.116), originality (p = 0.558, r = 0.076), or snapshot scores (p = 0.603, r = 0.068). Results question whether deceptive thinking for a military context can be improved by a visual aid containing prompts about military deception principles. However, some task elements (e.g., same hypothetical scenario/only rating the best stratagem) may have reduced/nullified potential differences between groups. The use of an existing military deception visual aid may be limited to military samples. Future studies could employ mixed-method approaches or gamified designs to investigate the potential to enhance military deception planning.